Evaluation of Sharia Property Design Criteria (Case Study: Housing Sharia Property Developer Community (DPS) in Malang City) - diana uswa; Iwan Wibisono (Jurnal Mahasiswa Jurusan Arsitektur, 2022)
Indonesian people in responding to the development of nature, of course have a different perspective and attitude. For the Muslim community, which incidentally is the largest population in Indonesia, they have a tendency to choose sharia residential objects as a decent and comfortable residential option. Sharia is not just a label, but between what is offered and what is obtained by the customer. Among them are sharia property residential objects in Malang City which are under the auspices of the Sharia Property Developer community (DPS), with a sharia contract scheme and a safe business scheme. With the issue of sharia property occupancy, it is necessary to conduct research "Evaluation of Sharia Property Design Criteria" so that decent and comfortable housing is achieved. In this study, the method that will be used is descriptive quantitative method using AHP with expert validation related to the concepts and criteria of sharia property occupancy. The result of this research is the weighting of the case study of Sharia Property Developer (DPS) housing which was studied in Malang City.